More-than-Human Geography: Core Issues and Trends - Wu, Lei (International Journal of Social Sciences and Public Administration, 2025)
In the 21st century, in the trend of ‘returning to materialism’ in Western geography, More-than-Human Geography (MTHG) has emerged as one of the most important ways of exploring the world constituted by human and non-human beings. Through the analysis of relevant journal articles and books, the review finds that there are obvious differences between domestic and international research on MTHG: the West focuses on ecological politics and climate ethics with an ontological revolution as the core, while China focuses on the materialistic turn and localised application. As one of the most groundbreaking theoretical paradigms in human geography in the 21st century, MTHG dissolves the dichotomy between natural determinism and social constructivism, reconstructs the spatial cognitive paradigm of dynamic correlation, and provides a technological and ethical framework for cross-species collaboration in urban planning and ecological restoration.